Neuromuscular strategies contributing to faster multidirectional agility performance - Spiteri, T.; Newton, R. U.; Nimphius, S. (Journal of Electromyography and Kinesiology, 2015)
The aim of this study was to first determine differences in neuromuscular strategy between a faster and slower agility performance, and second compare differences in muscle activation strategy employed when performing two closely executed agility movements. Participants recruited from an elite female basketball team completed an ultrasound to determine quadriceps muscle-cross sectional area; reactive isometric mid-thigh pull to determine the rate of muscle activation, rate of force development, pre-motor time and motor time; and multidirectional agility tests completing two directional changes in response to a visual stimulus. Peak and average relative muscle activation of the rectus femoris, vastus medialis, vastus lateralis, biceps femoris, semitendinosus and gastrocnemius were measured 100 ms prior to heel strike (pre-heel strike) and across stance phase for both directional changes. Faster agility performance was characterized by greater pre-heel strike muscle activity and greater anterior muscle activation during stance phase resulting in greater hip and knee extension increasing propulsive impulse. Differences between directional changes appear to result from processing speed, where a greater delay in refractory times during the second directional change resulted in greater anterior muscle activation, decelerating the body while movement direction was determined.